2021
DOI: 10.1002/advs.202103229
|View full text |Cite
|
Sign up to set email alerts
|

Phonon‐Related Monochromatic THz Radiation and its Magneto‐Modulation in 2D Ferromagnetic Cr2Ge2Te6

Abstract: Searching multiple types of terahertz (THz) irradiation source is crucial for the THz technology. In addition to the conventional fermionic cases, bosonic quasi-/particles also promise energy-efficient THz wave emission. Here, by utilizing a 2D ferromagnetic Cr 2 Ge 2 Te 6 crystal, first a phonon-related magneto-tunable monochromatic THz irradiation source is demonstrated. With a low-photonic-energy broadband THz pump, a strong THz irradiation with frequency ≈0.9 THz and bandwidth ≈0.25 THz can be generated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Around and below T 1 ≈ 100 K, the phonon lifetime = c 1 2 (FWHM) is the longest, about 1.1−1.5 ps, where c is the velocity of the light. A recent THz spectroscopy study on CGT reported τ ≈ 1.15− 1.11 ps 26 along with an attenuation of FWHM due to the formation of magnetic correlations below the spin fluctuation temperature of 160 K. 26 In pristine CGT, it has been reported that lattice parameter α demonstrates the onset of a negative thermal expansion around T 1 . 1b,27 Hence, we can infer that the enhancement of τ of in-plane vibration (E g 4 mode) (see Figure 5 (b)) occurs due to the reduced phonon−phonon interactions because of lattice expansion in the ab-plane with decreasing temperature.…”
Section: Anharmonicitymentioning
confidence: 99%
“…Around and below T 1 ≈ 100 K, the phonon lifetime = c 1 2 (FWHM) is the longest, about 1.1−1.5 ps, where c is the velocity of the light. A recent THz spectroscopy study on CGT reported τ ≈ 1.15− 1.11 ps 26 along with an attenuation of FWHM due to the formation of magnetic correlations below the spin fluctuation temperature of 160 K. 26 In pristine CGT, it has been reported that lattice parameter α demonstrates the onset of a negative thermal expansion around T 1 . 1b,27 Hence, we can infer that the enhancement of τ of in-plane vibration (E g 4 mode) (see Figure 5 (b)) occurs due to the reduced phonon−phonon interactions because of lattice expansion in the ab-plane with decreasing temperature.…”
Section: Anharmonicitymentioning
confidence: 99%
“…The preparation of high-quality 2D magnetic materials is of great significance for understanding their physical properties, magnetic regulation, and even spintronics applications. These magnetic materials are most prepared by the methods of mechanical exfoliation [36,140], chemical vapor deposition (CVD) [141,142], liquid-phase exfoliation [143], selfflux method [55,85,144,145], solution synthesis [146], and molecular beam epitaxy (MBE) [40,44,97].…”
Section: Experimental Progresses For Typical Fm Semiconductorsmentioning
confidence: 99%
“…In addition, the bulk CrXTe 3 single crystal also exhibit some novel physical phenomena, such as existence of a two-step magnetic order in the anisotropy of CrXTe 3 [85], an insulator-metal and structural transition at 7.5 GPa in CrSiTe 3 [160], multiple domain structure and symmetry types in CrGeTe 3 [144], coexistence of large positive magnetoresistance and negative magnetoresistance in CrSiTe 3 [161], ultra-long remagnetization behavior in the CrGeTe 3 [162], phonon-related magneto-tunable monochromatic THz irradiation [145].…”
Section: Crxtementioning
confidence: 99%
“…There has been a wealth of research into THz generation methods, namely, difference-frequency generation (DFG) with multi-color laser pulses , and optical rectification (OR) of a single broadband optical pulse in nonlinear crystals. , A range of materials, including semiconductors, , organic crystals, and ferromagnets, have been examined with demonstration of both high-energy single-cycle and multi-cycle THz pulses. For DFG, the central emission frequency and bandwidth rely on the difference between the wavelengths of the optical pulses used.…”
Section: Introductionmentioning
confidence: 99%